The Effect of Location, Service Quality, and Store Atmosphere on purchasing decisions at gedoh Coffee Singojuruh - Aulia, Jiean Okta; Riyanto, Agus; Aini, Winda Hurotul (Neo Journal of economy and social humanities, 2024)
This study aims to analyze the effect of location, service quality, and store atmosphere on purchasing decisions at Gedoh Coffee Singojuruh, both simultaneously and partially. The population in this study were consumers who made purchases at Gedoh Coffee Singojuruh. The sampling method used is non probability sampling, data collection using accidental sampling. Data is collected by observation, questionnaires, interviews, and documentation. Where sampling is 40 respondents. This type of research is quantitative descriptive using multiple linear regression analysis, coefficient of determination, hypothesis testing, namely partial test (t test), and simultaneous test (F test), and classical assumption test, namely normality test, multicollinearity, and heteroscedasticity test. Based on the SPSS results obtained, the value of multiple linear regression analysis is 0.768, this means that the proportion of variation in the Purchasing Decision variable can be explained by the Location, Service Quality, and Store Atmosphere variables by 76.8%, while the remaining 23.3% is explained by other variables. The results of this study found that Location, Service Quality, and Store Atmosphere simultaneously have a positive and significant effect on Purchasing Decisions at Gedoh Coffee Singojuruh.